THE INFLUENCE OF STRUCTURAL DEFECTS ON THE KINETICS OF DIFFUSION PROCESSES - Т. E. Sarkarov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
At present there are various methods of control, based on various physical principles and possessing a wide variety of different sensitivity, diversity of applications.